Latrophilin signaling links anterior-posterior tissue polarity and oriented cell divisions in the C. elegans embryo. - Langenhan, T; Prömel, S; Mestek, L; Esmaeili, B; Waller-Evans, H; Hennig, C; Kohara, Y; Avery, L; Vakonakis, I; Schnabel, R; Russ, A (2009)
Understanding the mechanisms that coordinate the orientation of cell division planes during embryogenesis and morphogenesis is a fundamental problem in developmental biology. Here we show that the orphan receptor lat-1, a homolog of vertebrate latrophilins, plays an essential role in the establishment of tissue polarity in the C. elegans embryo. We provide evidence that lat-1 is required for the alignment of cell division planes to the anterior-posterior axis and acts in parallel to known polarity and morphogenesis signals. lat-1 is a member of the Adhesion-GPCR protein family and is structurally related to flamingo/CELSR, an essential component of the planar cell polarity pathway. We dissect the molecular requirements of lat-1 signaling and implicate lat-1 in an anterior-posterior tissue polarity pathway in the premorphogenesis stage of C. elegans development.